Tanggungjawab Negara Bendera Kapal Terhadap Perbudakan ABK Indonesia - Ahriani Ahriani; Josina Augustina Yvonne Wattimena; Arman Anwar (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Until now, there are still many cases of crew members who receive inhuman treatment and even include slavery, apart from receiving inhuman treatment, the crew members also do not get a salary in accordance with the work agreement. Slavery is a gross human rights violation because it undermines human dignity. Based on the facts of migrant workers, especially Indonesian crew members, it shows that the treatment received by Indonesian crew members is not in accordance with the provisions of international conventions and Indonesian national regulations.Purposes of the Research: This paper aims to find out how international law regulates the prohibition of slavery on ships and the responsibility of the flag state of ships in cases of Indonesian crew slavery.Methods of the Research: The method used in this research is the type of normative juridical research method, the type of descriptive analytical research, the source of legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. Legal Material Analysis and Legal Material Analysis Methods.Results of the Research: The results obtained are that basically international law has regulated and provided legal protection for ABK. International legal arrangements regarding the prohibition of slavery on board are contained in the international legal instruments CAT (Convention against Torture and Other Cruel, Inhuman and Degrading Treatment or Punishment), CERD (International Convention on the Elimination of All Forms of Racial Discrimination), UDHR (Universal Declaration of Human Rights), and ILO (International Labor Organization). The responsibility of the flag state of the ship in the case of Indonesian crew slavery. that any problem arising from a ship with the flag of its State, the country concerned is obliged to effectively exercise its jurisdiction and control, investigate and carry out inspection of the vessel concerned In the case of slavery for Indonesian crew members, which involves the State of Indonesia and China, the two countries must cooperate in examining the case, in this case the slavery case that occurred against Indonesian crew members.